Calibration of a sedimentation model through a continuous genetic algorithm - Coronel, Anibal; Berres, Stefan; Lagos Aguilera, Richard Adolfo (My University, 2019)
In this contribution we consider the problem of flux identification in a scalar conservation law modelling the phenomenon of sedimentation. The experimental observation data used for the calibration consist of a solid concentration profile at a fixed time. The identification problem is formulated as an optimization one, where the distance between the profiles of the model simulation and observation data is minimized by a least squares cost function. The direct problem is approximated by a monotone finite volume scheme. The numerical solution of the calibration problem is obtained by a continuous genetic algorithm. Numerical results are presented in order to validate the efficiency of the proposed algorithm.
Keywords: continuous genetic algorithms; calibration; parameter identification; inverse problems